Experimental study of the characterization of household waste in Bamako, Mali - Adamou, Mohamadou; Maiga, Mohamed S; Cissé, Oumar; Sagara, Joseph Amadomon; Ouattara, Yaya (International Journal of Environment, Agriculture and Biotechnology, 2023)
In Bamako, the flow of household waste and its typology are little known. In order to set up a sustainable management system for the city's garbage, it is nevertheless important to know the quantities, natures and dimensions of the objects that make up the garbage. This study, which began in 2017, consisted of characterizing the garbage collected at the household level in Bamako using the MODECOM method modified to adapt it to the Malian context. The objective of this study was to propose a method intended to obtain solid results on the characteristics of household waste produced in Bamako in order to build adapted collection and recovery strategies. The results, obtained from a sample of 270 households in the 6 communes of Bamako and 3 neighborhoods of different socio-economic levels per commune, showed that the average ratio of household waste produced in Bamako is about 0.28 Kg per inhabitant per day. The category of fines is the most important, with an average daily production of 2.45 kg for a household with an average of 20.5 inhabitants. Putrescibles come in second place. Their production represents 41% of the average amount of garbage generated in a high standard household. It represents the main biodegradable category of garbage. Fines, which are mostly sand, charcoal and ash, accounted for 37 percent of the waste generated by households of the same type. The particle size sorting, which can help to choose suitable industrial sorting tools, shows that the fraction of medium-sized garbage is the most abundant. The data from the characterization of garbage would allow the development of all forms of garbage management strategies, especially for its collection and recovery.